Supine traction vs fulcrum bending radiographs in preoperative imaging of scoliosis patients treated with magnetically controlled growing rods (MCGR): which technique is better to predict surgical correction of the main curve? - Hemmer, Stefan; Trefzer, Raphael; Renkawitz, Tobias; Pepke, Wojciech (Global spine journal, 2025)
Study Design Retrospective Cohort Study. Objectives Flexibility radiographs such as traction or bending radiographs are essential in preoperative imaging to assess for curve flexibility and to estimate the amount of operative correction in order to determine the type and length of instrumentation in growth-accompanying scoliosis treatment. Both traction and bending radiographs are controversially discussed in the literature. The predictability of flexibility radiographs of postoperative main curve correction specifically in patients treated with magnetically controlled growing rods (MCGR) has not yet been studied. Methods Juvenile patients with idiopathic or neuromuscular scoliosis that were surgically treated with a primary MCGR implant with pedicle screw fixation between 2018-2022 were retrospectively registered. Patients that underwent prior spine surgery, with supine lying-down radiograph and patients with missing traction or bending radiographs available were excluded. Image analysis was conducted using Surgimap (R) software. For statistical analysis, t test and ANOVA analysis were used to compare the means between groups with a significance level set at P < 0.05. Results A total of 50 patients, 34 diagnosed with idiopathic scoliosis (IS) and 16 diagnosed with neuromuscular scoliosis (NMS), were included. Globally, main curve Cobb angles were significantly higher in supine traction compared to fulcrum bending images (44.8 degrees vs 39.6 degrees; P < 0.001) and in the IS subgroup (42.4 degrees vs 37.3 degrees; P < 0.001). Compared to postoperative images, significant differences of supine traction but not fulcrum bending radiographs were detected in total (P < 0.001; P = 0.20) as well as IS (P < 0.001; P = 0.32) and NMS (P < 0.001; P = 0.44) subgroups. Fulcrum bending images displayed significantly higher flexibility rates (FR) and flexibility index (FI) compared to traction images in total (FR: 42.9 vs 35.2, P < 0.001; FI: 1.08 vs 1.58, P = 0.024) and the IS subgroup (FR: 44.2 vs 35.8, P < 0.001; FI: 1.19 vs 1.43, P = 0.033). Conclusions Fulcrum bending radiographs showed better flexibility and prediction of operative main curve correction compared to supine traction radiographs in total and IS subgroup. Fulcrum bending might be more precise for predicting the postoperative main curve correction potential of primary MCGR surgery in IS patients.
Gesehen am 26.02.2025